Crossing the rubicon : the decline of the American empire at the end of the age of oil - Ruppert, Michael C.; Hecht, Jamey, ed. (Canada : New Society Publishers, 2004)
The attacks of September 11, 2001 were accomplished through an amazing orchestration of logistics and personnel. This book claims to discover and identify key suspects--some in the highest echelons of American government--by showing how they acted in concert to guarantee the desired result. The author offers an interdisciplinary analysis of petroleum, geopolitics, narco-traffic, intelligence and militarism--without which 9/11 cannot be understood: The US manufacturing sector has been mostly replaced by speculation on financial data whose underlying economic reality is a dark secret. America's global dominance depends on a continually turning mill of guns, drugs, oil and money. Oil and natural gas--the fuels that make economic growth possible--are subsidized by American military force and foreign lending. In reality, 9/11 and the resulting "War on Terror" are parts of a massive authoritarian response to an emerging economic crisis of unprecedented scale. Peak Oil--the beginning of the end for our industrial civilization--is driving the elites of American power to implement unthinkably draconian measures of repression, warfare and population control.--From publisher description.
Keywords: Petroleum industry and trade -- United States; September 11 terrorist attacks, 2001; Political corruption -- United States; United States -- Politics and government -- 2001-2009; United States -- Foreign relations -- 2001--